Esvoc” Educatif Game for Learning Vocabulary toward the Junior High School Students - Winarsih; Abdi Pandu Kusuma (Universitas Islam Balitar, 2021)
This research is purposed to develop an Educatif Game for learning vocabulary toward the Junior High School Students in Blitar City. The game application was created to help the students easily learn vovabulary, improve their vocabulary mastery and enjoy their English learning. The researh was categorized as Research and Development Research (R & D). The research design and development was based on Sugiyono’s model. The steps of development were: 1) potential and problem solution, 2) collecting data, 3) product design, 4) design validation, 5) design revision, 6) trial product, 7) product revision, 8) trial usage, 9) product revision, and 10) mass production. To collectt the data, the researcher did an interview, giving questionnare, and doing documentation. Descriptive qualitative was taken to analyze the data. The result of media validation in the average of 88%. This score categorized as “very good” with the interval 80%-100%. It could be concluded that the product result of game was categorized as an excellent product and valid. In the other word. The product is proper used and be applied for learning vocabulary to the junior high school students